Контактне деформування складеного індуктора із допоміжним екраном при дії електромагнітного поля - Альтенбах, Хольм; Лавінський, Денис Володимирович; Науменко, Костянтин (НТУ "ХПІ", 2017)
У статті обговорюються питання розрахунків напружено деформованого стану складеного багатовиткового індуктора із допоміжним екраном, який призначено для притягнення тонкостінних заготовок за умов технологічних операцій МІОМ. Для розв’язання використовується чисельний метод, що засновано на методі скінчених елементів. Для врахування контактної взаємодії використано спосіб введення шарів контактних елементів. За результатами аналізу визначені раціональні значення деяких конструкційних параметрів.

The paper discusses issues concerning the deformation of a system of conductive bodies under the action of the electromagnetic field. Problem of nonlinear deformation of the compound coil with an assistant for electromagnetic forming of sheet workpieces is considered as a practical application. The problem is solved by the finite element method. Contact interaction is modeled by the introduction of special layers of contact finite elements. Spatial-temporal distributions of the main components of the electromagnetic field are obtained. The ability to review the problem of deformation in the quasi-stationary formulation is justified. The distribution of the main component of the stress-strain state is presented. The influence of the current magnitude at the maximum stresses is evaluated.
Contact deformation of the compound coil with an assistant screen under the action of electromagnetic field
Keywords: напружено-деформований стан; метод скінчених елементів; магнітно-імпульсна обробка; багатовитковий індуктор; stress-strain state; finite element method; electromagnetic forming; electromagnetic field